Use of Experience Sampling Method in the Assessment of Anxiety Disorders: A Systematic Review - Büşra Yıldırım; Gizem Bozyel; Orçun Yorulmaz (Psikiyatride Güncel Yaklaşımlar, 2020)
The Experience Sampling Method (ESM), which makes possible to make momentary assessment during daily life by using portable devices and applications, has been actively used in clinical psychology research along with accelerating technological developments in recent years. The use of this method might be highly functional in some problems characterized with fluctuating symptom severity such as anxiety disorders. Because it is aimed to investigate the current literature findings about the use of this method in research on anxiety disorders and to make inferences about main study findings in this systematic review, current empirical studies particularly on anxiety disorder symptoms performed with the ESM were screened and examined. Taking the recent DSM-5 revisions into account, specific keywords were determined and scanned in 4 different databases (Web of Science, ProQuest, PsycINFO and PubMed). Following the screening processes, 14 articles that matched with inclusion criteria were involved in the present study. Firstly, it is seen that those studies were performed by using ESM generally included the adults and female participants and assessments with experience sampling measurements by electronic devices took 9 days in avarage. Moreover, it is also observed that among the different categories of psychological disorders, were evalutions on momentary affect changes, post-event processing and rumination that were usually studied. In sum, it is considered that ESM is a functional method that can be used in the field of scientific research, and it may be beneficial that recognizing and extending the utilization of this method.